Marine Phytoplankton Improves Exercise Recovery in Humans and Activates Repair Mechanisms in Rats - Sharp, Matthew H.; Sahin, Kazim; Stefan, Matt W.; Gheith, Raad H.; Reber, Dallen D.; Ottinger, Charlie R.; Orhan, Cemal; Tuzcu, Mehmet; Sahin, Nurhan; Lowery, Ryan P.; Durkee, Shane; Wilson, Jacob M. (International Journal of Sports Medicine, 2020)
This study investigated the effects of marine phytoplankton supplementation on 1) perceived recovery and ground reaction forces in humans following a non-functional overreaching resistance-training program and 2) myogenic molecular markers associated with muscle cell recovery in a rat model. In the human trial, a 5-week resistance-training program with intentional overreaching on weeks 2 and 5 was implemented. Results indicate that marine phytoplankton prompted positive changes in perceived recovery at post-testing and, while both marine phytoplankton and placebo conditions demonstrated decreased peak and mean rate of force development following the overreaching weeks, placebo remained decreased at post-testing while marine phytoplankton returned to baseline levels. In the rat model, rats were divided into four conditions: (i) control, (ii) exercise, (iii) exercise + marine phytoplankton 2.55 mg·d-1, or (iv) exercise+marine phytoplankton 5.1 mg·d-1. Rats in exercising conditions performed treadmill exercise 5 d·wk-1 for 6 weeks. Marine phytoplankton in exercising rats increased positive and decrease negative myogenic factors regulating satellite cell proliferation. Taken together, marine phytoplankton improved perceptual and functional indices of exercise recovery in an overreaching human model and, mechanistically, this could be driven through cell cycle regulation and a potential to improve protein turnover.
Keywords: overreaching; satellite cells; myostatin; recovery; resistance-training; performance